English songs to develop vocabulary in 7 th graders at Unidad Educativa Península De Santa Elena. - Mendoza Almagro, Kenia Jesús (2024)
Teaching vocabulary with English songs could be a fun technique. At the same time, the use of songs in class as an encouragement to develop vocabulary is a topic that has not received much coverage. The present research aims to know the technique of English songs on the vocabulary development of 7th graders. It will involve a sample of English teachers from diverse backgrounds and will utilize qualitative research methods such as one-on-one interview. The project seeks to indagate the teacher´s perceptions of English songs to develop vocabulary and experiences regarding this approach. The findings of this research will contribute to the existing literature on language learning techniques in English as a foreign language (EFL) and provide valuable insights for educators and curriculum developers seeking innovative techniques to enhance vocabulary acquisition in 7 th graders.